Advances in population monitoring of the mangrove ‘uçá’-crab (Ucides cordatus): reduction of body size variance for better evaluation of population structure and extractive potential - Pinheiro, Marcelo A. A. [UNESP]; Sousa, Fernanda V. B. [UNESP]; Perroca, Julia F. [UNESP]; Silva, Mauro M. T.; Souza, Raimundo L. M.; Mota, Thais A.; Rocha, Sérgio S. (Taylor & Francis, 2023)
Monitoring focusing on target species is an important tool to better understand biodiversity. The density, size, extractive potential and population structure of Ucides cordatus reflects the conservation of the mangrove ecosystem. The Federal Brazilian Institution of Biodiversity Conservation (ICMBio) defined a protocol to standardize and estimate these parameters using an indirect method that does not depend on the capture of individuals of a species. In this protocol are used models to adjust diameter of crabs' gallery (DG) measures into largest carapace width (LC). Because this relationship (LC vs. DG) can differ according to geographic positions, the present study assessed it in three Brazilian mangrove areas (north, north-east, and south-east regions). Linear models of this relationship were compared between sexes, and also applied as a single model considering these Brazilian localities as a fixed factor and in three independent models for each locality separately. Equations did not differ significantly between sex and could be represented as one to each locality. However, a simpler linear model not including mangroves as fixed factors can be used to represent the entire latitudinal gradient, promoting a homogeneity of the estimation error, due to cover the entire body size (LC) variation of the Ucides cordatus crab.
Keywords: Biometry; conservation; fishery management; monitoring; sustainable development